Pengaruh Digital Payment Terhadap Perilaku Konsumtif Mahasiswa Fakultas Keguruan dan Ilmu Pendidika Universitas Mulawarman - Irman, Dwi Agust Subriana; Sutrisno, Sutrisno; Reza, Reza (Jurnal Ilmiah Wahana Pendidikan, 2024)
The development of technology and information is now starting to be felt by the number of payment systems, especially digital payments. Initially, digital payments were issued through payment cards in the form of credit cards as a substitute for cash payments. However, digital payments in Indonesia are experiencing changes with the presence of mobile banking or electronic money. As a result, almost all economic activities already use electronic money as a means of payment, so that with the ease of making transactions using digital payments, it is easier for people to spend their money, which will offer a more efficient or consumptive lifestyle. This research aims to determine the influence of Digital Payment on the consumer behavior of FKIP students at Mulawarman University. This research method is descriptive quantitative using data collection techniques through questionnaires. The population in this study was Mulawarman University FKIP students, totaling 6,145 students with a sample size of 98 students. The sampling technique in this research used purposive sampling. The analysis technique used is simple linear regression analysis with the SPSS version 26 application. The results of this research show that from the results of partial test calculations or t tests on Digital Payment, the t count results are 6.742 > t table 1.985 with a significance of 0.000 < 0.05, which means that Digital Payment has a partial and significant effect on the consumer behavior of Mulawarman University FKIP students. The coefficient of determination reached 0.321 or 52.1%, which means that the Digital Payment variable influences the consumptive behavior of Mulawarman University FKIP students. Meanwhile, the remaining 67.9% was influenced by other factors outside this research. Thus the hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected.